Finding Various Exact Solutions for Zeldovich Equation in the Sense of Conformable Fractional Derivative with Constant Coefficients (Latakia University Journal -Basic Sciences Series, 2020)
This research aims to find explicit exact solutions for fractional partial differential Zeldovich equation with constant coefficients in the sense of conformable fractional derivative, by using the substitution Ricatti ordinary differential equation method and Feng's first integral method. These two methods give three types of analytical solutions, complex hyperbolic solutions, and complex trigonometric solutions and rational solutions according to the coefficients. The two methods are efficient and reliable, and its can be used as an alternative to establish new solutions of different types of fractional differential equations applied in mathematical physics.